Sexual Assault Disclosure: The Effect of Victim Race and Perpetrator Type on Empathy, Culpability, and Service Referral for Survivors in a Hypothetical Scenario - Franklin, Cortney A.; Garza, Alondra D. (Journal of interpersonal violence, 2021)
The aftermath of sexual assault warrants further attention surrounding the responses provided by those to whom survivors disclose, especially when perpetrator type or victim race may affect whether the bystander response is supportive or attributes culpability to the victim. Disclosure responses have significant consequences for survivors’ posttrauma mental health and formal help-seeking behavior. The current study used a sample of 348 self-report, paper-and-pencil surveys administered during the fall 2015 semester to a purposive sample of undergraduate students with a mean age of 20.94 years old at a midsized, Southern public university. Survey design included a randomly assigned 2 × 2 hypothetical sexual assault disclosure vignette. The objective of the study was to assess the effect of perpetrator type (stranger vs. acquaintance) and victim race (White vs. Black) on empathic concern, culpability attributions, and resource referral. Between-subjects factorial ANOVA and multivariate ordinary least squares (OLS) regression models were estimated to identify the role of vignette manipulations, participant-sexual victimization history, and rape myth acceptance on empathy, culpability, and resource referral for the sexual assault survivor portrayed in the vignette. Multivariate analyses included main effects and moderation models. Findings revealed increased culpability and decreased resource referral for victims of acquaintance rape as compared with stranger rape, independent of victim race. Although no direct victim race effects emerged in the multivariate analyses, race moderated the effect of culpability on resource referral indicating culpability attributions decreased resource referral, but only when the victim was Black . Implications from the results presented here include a continued focus on bystander intervention strategies, empathy-building techniques, and educational programming targeting potential sexual assault disclosees and race stereotypes that disadvantage victims of color.